Electron Transfer of Myoglobin Immobilized in Au Electrodes Modified with a RAFT PMMA-Block-PDMAEMA Polymer. (31st August 2014) - Toledo, Carla N.; Florenzano, Fábio H.; Schneedorf, José M.
Abstract : Myoglobin was immobilized with poly(methyl methacrylate)-block-poly[(2-dimethylamino)ethyl methacrylate]PMMA-block-PDMAEMA polymer synthesized by reversible addition-fragmentation chain transfer technique (RAFT). Cyclic voltammograms gave direct and slow quasireversible heterogeneous electron transfer kinetics between Mb-PMMA-block-PDMAEMA modified electrode and the redox center of the protein. The values for electron rate constant (Ks ) and transfer coefficient (α ) were0.055 ± 0.01 ·s −1 and0.81 ± 0.08, respectively. The reduction potential determined as a function of temperature (293–328 K) revealed a value of reaction center entropy ofΔ S 0 of351.3 ± 0.0002 J·mol −1 ·K −1 and enthalpy change of- 76.8 ± 0.1 kJ·mol −1, suggesting solvent effects and charge ionization atmosphere involved in the reaction parallel to hydrophobic interactions with the copolymer. The immobilized protein also exhibits an electrocatalytical response to reduction of hydrogen peroxide, with an apparent Km of114.7 ± 58.7 μ M. The overall results substantiate the design and use of RAFT polymers towards the development of third-generation biosensors.